The impact of Chinese COVID-19 pandemic on the incidence of peripheral facial nerve paralysis after optimizing policies - Yu, Erhui; Jin, Fanyuan; Zhou, Wenhui; Chen, Junkang; Cai, Huafeng; Hu, Jinhua; Xuan, Lihua (Frontiers in Public Health, 2023)
Objective To evaluate the impact of the COVID-19 pandemic on the occurrence of Peripheral Facial Nerve Paralysis (PFNP) in Chinese patients, identify contributing factors, and explore the relationship between COVID-19 and PFNP. Methods We conducted a retrospective study covering the years 2020 to 2023, categorizing patients into three groups based on their visit dates: Group 1 (December 8, 2020 to February 28, 2021), Group 2 (December 8, 2021 to February 28, 2022), and Group 3 (December 8, 2022 to February 28, 2023). We collected and compared data on disease onset and patient characteristics among these groups. Results In Group 3, following the widespread COVID-19 outbreak, there was a significant increase of 22.4 and 12.1% in PFNP cases compared to the same periods in the preceding 2 years (p < 0.001). Group 3 patients were more likely to be aged between 30 and 60 years, experience onset within 7 days, present with Ramsay Hunt syndrome, and have a higher H-B score of VI compared to the previous 2 years (p < 0.017). Logistic regression analysis revealed a strong association between the COVID-19 pandemic and the incidence of Ramsay Hunt syndrome in PFNP (OR = 3.30, 95% CI 1.81–6.03, p < 0.001). Conclusion The incidence of PFNP increased in China after the COVID-19 pandemic, particularly in patients with Ramsay Hunt syndrome, indicating that COVID-19 infection can trigger and worsen PFNP.